Effects of Sm on Fe–Mn catalysts for Fischer–Tropsch synthesis. Issue 55 (10th October 2019) - Han, Zhonghao; Qian, Weixin; Ma, Hongfang; Zhang, Haitao; Sun, Qiwen; Ying, Weiyong
Abstract : The effect of samarium on iron-based catalysts for Fischer–Tropsch synthesis was investigated. Abstract : Sm-promoted FeMn catalysts were prepared by the co-precipitation method and characterized by N2 adsorption, XRD, CO-TPD, H2 -TPD, CO2 -TPD, H2 -TPR, XPS and MES. It was found that compared with the un-promoted catalyst, when Sm was added at a proper content, the catalyst showed a larger BET surface area and promoted the formation of iron particles with a smaller size. The presence of Sm could increase the surface charge density of iron, which enhanced the Fe–C bond and promoted the stability and amount of CO dissociated adsorption, as confirmed by XPS and CO-TPD. Furthermore, according to MES, Sm could promote the formation of Fe5 C2, which was the active phase of FTS. In addition, Sm could also enhance the basicity of the catalysts and suppress the H2 adsorption capacity, which inhibited the hydrogenation reaction and the conversion of olefins to paraffins, as verified by the results of CO2 -TPD and H2 -TPD. According to the FTS performance results, compared with the observations for the un-promoted catalysts, when the molar ratio of Sm to Fe was 1%, the CO conversion increased from 63.4% to 70.4%, the sum of light olefins in the product distribution increased from 26.6% to 32.6, and the ratio of olefins to paraffins increased to 4.18 from 4.09.